Flow and heat transfer in a meandering channel - Ibrahim, Syed; Khan Marwat, Dil Nawaz; Ullah, Naeem; Nisar, Kottakkaran Sooppy; Kamran, (Frontiers in Materials, 2023)
Fluid flows due to internal or external forces like wind, gravity, pressure gradients, side wall motion, MHD, and free convection. This study examines how meanders impact heat transfer by studying the behavior of viscus fluid flow with streamwise vortices in a sinusoidal wavy meandering channel of non-uniform radius. The study simplifies the motion and energy equations governing the fluid flow using novel transformations and regular perturbation method. By plotting graphs for different parameter values, such as Pr, Re, and Ec, the study reveals that decreasing the wavelength leads to flow separation near the channel surface. However, the stream moves forward with a sudden meander disturbance, causing the flow to become rectilinear and independent of vertex-generating centrifugal forces. The study identifies a stream function using standard and established relations. The fluid flow patterns and temperature distribution behavior is shown in various plots, highlighting the significant impact of meanders on fluid flow.